2002
DOI: 10.1096/fj.02-0272fje
|View full text |Cite
|
Sign up to set email alerts
|

Active heroin administration induces specific genomic responses in the nucleus accumbens shell

Abstract: Long-term drug-induced alterations in gene expression underlying neuroplasticity in the nucleus accumbens (NAc) may play a crucial role in relapse behavior in abstinent drug addicts. In this respect, stimulus-induced relapse behavior is considered as the retrieval of stored drug-related information. Because the NAc shell may determine the impact of external and internal stimuli on goal-directed behavior, we compared long-term gene expression in this brain region after active and passive administration of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 51 publications
1
51
1
1
Order By: Relevance
“…Here, we demonstrated that MPEP treatment in the NAc shell attenuated the heroin seeking behavior induced by context, which indicates the activation of mGluR5 in the NAc shell may be involved in context induced heroin seeking. With respect to opiate drugs, heroin administration leads to long-term alterations in gene expression in the NAc shell [31] . The mPFC is a brain area that has a pivotal role in relapse to opiate seeking during periods of drug absti- Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that MPEP treatment in the NAc shell attenuated the heroin seeking behavior induced by context, which indicates the activation of mGluR5 in the NAc shell may be involved in context induced heroin seeking. With respect to opiate drugs, heroin administration leads to long-term alterations in gene expression in the NAc shell [31] . The mPFC is a brain area that has a pivotal role in relapse to opiate seeking during periods of drug absti- Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence demonstrates that volitional (actively intended) drug intake produces distinct physiological, biochemical, and behavioral effects when compared with forced drug administration. For example, the response contingency of drug exposure robustly influences gene expression (Jacobs et al, 2002(Jacobs et al, , 2003(Jacobs et al, , 2005, neural activation (Chang et al, 1994;Peoples and West, 1996;Stuber et al, 2005), and resultant extracellular neurochemistry (Di Ciano et al, 1996;Hemby et al, 1997;Jacobs et al, 2003;Lecca et al, 2007;Orejarena et al, 2009;You et al, 2007). With specific regard to nicotine, differential effects of volitional SA vs forced drug administration have been observed on a 4 b 2 nAChR expression (Metaxas et al, 2010), cortical glutamatergic projection activity and plasticity mechanisms in the ventral tegmental area (VTA) (McFarland et al, 2003;You et al, 2007), and plasma corticosterone levels (Donny et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to opiate drugs, heroin administration leads to long-term alterations in gene expression in the NAc shell (Jacobs et al, 2002). At the cellular level, changes in neuronal connectivity and neuronal physiology have been observed after opiate exposure.…”
Section: Introductionmentioning
confidence: 99%